Dual Band PIFA for WLAN and WiMAX MIMO Systems for Mobile Handsets. (2016) - Halaoui, Mustapha El; Kaabal, Abdelmoumen; Asselman, Hassan; Ahyoud, Saida; Asselman, Adel
Abstract: A compact planar inverted-F antenna (PIFA) dual band two-unit multiple-input multiple-output (MIMO) antenna system withhigh isolation is developed. The proposed MIMO antenna that consists of two PIFA elements has the advantage of compactstructure and multi-band for mobile device. The proposed antenna can cover the frequency range from 2.36 GHz to 2.52 GHz and 5.05 GHz to 5.98 GHz, therefore, it includes applications: High Performance radio Local Area Network/2 (5.2 GHz/5.6 GHz), Wireless Local Area Network (2.4 GHz/5.2 GHz/5.8 GHz), Bluetooth (2.4 GHz) and Worldwide Interoperability for MicrowaveAccess (5.5 GHz). By integrating a +shaped slots in the ground plane, we can increase the isolation between elements of theproposed antenna. The maximum gain of the proposed MIMO-antenna is 10.07 dB at 2.44 GHz and 9.97 dB at 5.55 GHz.